Pertunjukan Tari Piring Kumun Sebagai Representasi Sosiologi Gender dan Upaya Pelestarian Adat Budaya Kerinci - Monita Precillia (SENDRATASIK UNP, 2023)
Piring Kumun Dance is one of the traditional arts of the Kumun people. The Piring Kumun Dance is often performed in community activities and traditional activities, the dancers are a mixture of male dancers and female dancers. This research has three objectives namely; First, knowing the form of the motion of the Piring Kumun dance. secondly knowing the traditional and societal views of female dancers, thirdly analyzing the position and existence (social) of women in the Kumun community. This study uses Lev Vygotsky's feminist and sociocultural theory. Sociocultural theory emphasizes the role of social interaction in a person's psychological development. The research method used is a qualitative method with a content analysis approach from Krippendorf, namely a method used to examine symbolic phenomena with the aim of exploring and expressing the observed phenomena which are the content, meaning and essential elements of the performance. On the other hand, this research also uses an ethnographic context, this is done because it has compatibility between the subjects studied, namely art and culture or traditions in a society based on local wisdom.